2017
DOI: 10.1007/s10585-017-9863-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and their role for T stage determination and lymph node metastasis in early colon carcinoma

Abstract: Worldwide, colon cancer is among the most common cancer entities. Understanding the molecular background is the key to enable accurate stage determination, which is crucial to assess optimal therapy options. The search for preoperative biomarkers is ongoing. In recent years, several studies have proposed a diagnostic and prognostic role for miRNAs in cancer. Aim of this study was to evaluate miRNA expression patterns correlating with tumor stage, especially lymph node metastasis, in primary colon carcinoma tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…However, in glioma 24 and leukemia 25 , the expression of miR-152-3p was reported to be elevated in cancer tissue and cells, which is significantly higher than that in normal tissue and cells. Interestingly, there is a study revealing that miR-152-3p is differentially expressed in different T_stages (T1-T4) of colon cancer, with increased expression in T2-T4 and relatively higher expression in T2 and T4 26 . In this study, bioinformatics analysis and qRT-PCR revealed that miR-152-3p was markedly elevated in colon cancer tissue and cells, and silencing miR-152-3p led to decreased cell proliferation but increased cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in glioma 24 and leukemia 25 , the expression of miR-152-3p was reported to be elevated in cancer tissue and cells, which is significantly higher than that in normal tissue and cells. Interestingly, there is a study revealing that miR-152-3p is differentially expressed in different T_stages (T1-T4) of colon cancer, with increased expression in T2-T4 and relatively higher expression in T2 and T4 26 . In this study, bioinformatics analysis and qRT-PCR revealed that miR-152-3p was markedly elevated in colon cancer tissue and cells, and silencing miR-152-3p led to decreased cell proliferation but increased cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-548c-5p, miR-548i and miR-548am-5p were identified as the top three of 26 differentially expressed miRNAs with regard to lymph node metastasis [53]. But some other studies report no significant correlations of miRNA-expression patterns with CRC tumour stage by a miRNA microarray analysis [54]. The difference in conclusions is probably due to different detection approaches and tumour sample heterogeneity.…”
Section: Mirnas For Crc Diagnosis Treatment and Recurrence Predictionmentioning
confidence: 99%
“…Furthermore, the incidence of colon cancer continues to increase among persons under the age of 50, and the risk rises with age. The advancements in cancer detection and therapy, however, have not brought substantial increment in survival time of colon cancer patients [ 3 , 4 ]. It is imperative to explore useful biomarkers to improve the colon cancer therapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%